The Story of My Struggle - Malik, Tajammal Hussain Maj. Gen. (Lahore, Pakistan Jang Publishers, 1991)
Autobiography of a retired major general of the Pakistan Army, who was tried and imprisoned in 1980 on charges of trying to overthrow Gen. Zia-ul-Haq's martial law government
Include Illustration
Keywords: Pakistan -- Politics and government -- Malik, Tajammal Hussain